Body-skin-language. Syphilis in the field of enunciation of clinical dermatology [Cuerpo-piel-lenguaje. La sífilis en el campo de enunciación de la dermatología clínica] (2019)
This text poses a question regarding the body as a space of medical representation, linked to the disease’s deforming effects on it in the second half of the 19thcentury, as an archive in a Colombian-Spanish documentary series. The disease produces a sound, which when listened to, tells of the traces on the body’s unsettling landscape: skin. Thus the text reveals the speaking bodies that howl about the intersubjective experiences of the disease through the mediation between doctor and patient, in which a wise discourse captures the symptoms of the pain spread over the skin of the sufferer. The latter emerges and lends a voice to their subjective experience as a platform for expression for clinical dermatological taxonomies in the second half of the 19thcentury. © Esta obra está protegida bajo una Licencia Creative Commons Atribución-NoComer-cial 4.0 Internacional.